(untitled) (Bangladesh Journal of Pharmacology, 2010)
Three pyrazolone derivativeswith pyrazole ring extensionwere synthesized from ciprofloxacin by treating the parent compound with hydrazine derivatives. All the products have been characterized by IR and 1H-NMR spectral analysis. These derivatives showed potential cytotoxicity against brine shrimp nauplii than the ciprofloxacin.